A Researcher’s Guide to the Measurement and Modeling of Puberty in the ABCD Study® at Baseline - Cheng, Theresa W.; Magis-Weinberg, Lucía; Guazzelli Williamson, Victoria; Ladouceur, Cecile D.; Whittle, Sarah L.; Herting, Megan M.; Uban, Kristina A.; Byrne, Michelle L.; Barendse, Marjolein E. A.; Shirtcliff, Elizabeth A.; Pfeifer, Jennifer H. (Frontiers in Endocrinology, 2021)
The Adolescent Brain Cognitive Development℠ (ABCD) Study is an ongoing, diverse, longitudinal, and multi-site study of 11,880 adolescents in the United States. The ABCD Study provides open access to data about pubertal development at a large scale, and this article is a researcher’s guide that both describes its pubertal variables and outlines recommendations for use. These considerations are contextualized with reference to cross-sectional empirical analyses of pubertal measures within the baseline ABCD dataset by Herting, Uban, and colleagues (2021). We discuss strategies to capitalize on strengths, mitigate weaknesses, and appropriately interpret study limitations for researchers using pubertal variables within the ABCD dataset, with the aim of building toward a robust science of adolescent development.